Ekstrakulikuler Seni Tari dalam Mempengaruhi Kreativitas Siswa Sekolah Dasar Negeri 4 Rappang - Syakhruni, Syakhruni; Jalil, Jalil (Seminar Nasional LP2M UNM, 2023)
Abstract. This study aims to answer the problem of learning dance extracurricular activities at SDN 4 Rappang and learning dance in influencing creativity in extracurricular activities at SDN 4 Rappang. This type of research is descriptive qualitative research. The subjects of this study were students who joined the extracurricular activities of SDN 4 Rappang. This research study focuses on the implementation of dance learning in extracurricular activities at SDN 4 Rappang, which includes what the material is taught, the methods used in learning dance in relation to the creativity of students' movements. Keywords: Extracurricular Activities, Dance, Creativity